A chemometric approach for prediction of antifungal activity of some benzoxazole derivatives against Candida albicans - Podunavac-Kuzmanović Sanja O.; Jevrić Lidija J.; Kovačević Strahinja Z.; Kalajdžija Nataša D. (Acta Periodica Technologica, 2012)
The purpose of the article is to promote and facilitate prediction of antifungal activity of the investigated series of benzoxazoles against Candida albicans. The clinical importance of this investigation is to simplify design of new antifungal agents against the fungi which can cause serious illnesses in humans. Quantitative structure activity relationship analysis was applied on nineteen benzoxazole derivatives. A multiple linear regression (MLR) procedure was used to model the relationships between the molecular descriptors and the antifungal activity of benzoxazole derivatives. Two mathematical models have been developed as a calibration models for predicting the inhibitory activity of this class of compounds against Candida albicans. The quality of the models was validated by the leave-one-out technique, as well as by the calculation of statistical parameters for the established model. [Projekat Ministarstva nauke Republike Srbije, br. 172012 i br. 172014]